Cartera vencida de la Empresa Pública Municipal Terminal Terrestre, Tránsito y Seguridad Vial del cantón Babahoyo en el periodo 2021 - Chimbo Galarza, Marlon Steeven (2023)
The overdue portfolio represents all those values that the clients owe to the company and that must be managed because it can trigger financial problems for the organizations. The management of the overdue portfolio is one of the main problems presented by the public company, whose collection policies are not entirely effective. In general, this problem is generated due to inadequate collection processes and policies that do not allow a prompt return of overdue accounts. Therefore, the objective of this study is to determine the overdue portfolio of the Babahoyo Terminal Terrestre, Transit and Road Safety Municipal Public Company, for the period 2021. The methodological framework was made up of: a mixed approach, the methods used were inductive and deductive. In the work, the types of documentary and field research were also applied and the techniques to obtain information were interview and documentary analysis, through the instruments: questionnaire of questions addressed to a representative of the company and financial reasons to determine the turnover of accounts receivable. The results revealed that the weaknesses that were established regarding the management of the overdue portfolio in the company Transvial EP are based on the fact that they do not establish policies, goals or objectives for the reduction of the indicator. The main weaknesses that the company presents in relation to collection management are: not having an organic structure where a dependency and human talent responsible for collection management are established.